COMPARISON OF LIPID LOWERING EFFECT OF EXTRA VIRGIN OLIVE OIL AND ATORVASTATIN IN DYSLIPIDEMIA IN TYPE 2 DIABETES MELLITUS - Khan, Tariq Mahmood; Iqbal, Sohail; Rashid, Muhammad Adnan (Journal of Ayub Medical College Abbottabad, 2017)
Background: Extra virgin olive oil (EVOO) is fruit oil with rich source of monounsaturated fats and powerful antioxidants. It acts as hypolipidemic agent and significant decrease of plasma lipids levelwas observed with EVOO use. Atorvastatin is hypolipidemic drug commonly used for treatment of hyperlipidaemia. The purpose of this study was to determine & compare the lipid lowering effect of EVOO with atorvastatin in type 2 diabetic dyslipidaemia which is leading cause of microvascular diseases. Methods: This cross-sectional study was conducted on 60 already diagnosed cases of type 2 diabetes mellitus with dyslipidaemia. All sixty subjects were divided into 2 groups. Atorvastatin 40mg was given to Group One and two tablespoons of extra virgin olive oil orally per day was given to Group Two. Blood was collected for estimation of plasma lipids level at base line, 4th week, and 6th weeks in two groups and was compared statistically. Results: The present study demonstrated 20-40% lipid lowering effect of atorvastatin on plasma lipids level with 9-16% increase in HDL while extra virgin olive oil showed 14 to 25% reduction in plasma lipids with 8-12% increase in HDL-cholesterol level. Conclusion: This study concludes that both atorvastatin and extra virgin olive oil are effective in reducing plasma lipids level in type 2 diabetic dyslipidaemia with more prominent effect of atorvastatin than EVOO. Keywords: Extra virgin olive oil (EVOO); Atorvastatin; Diabetic dyslipidaemia